Developing a novel sensor technology for detecting neural activity based on surface plasmon resonance - Howe, Carmel Leah (2018)
One of the main goals of contemporary systems neuroscience is to understand how sensory inputs are processed, networks are formed and the resulting functional outputs. To achieve this, a recording technique is required that can detect action potentials with single-cell resolution for a long period of time across a large network. Current imaging techniques available are limited in at least one of the four elements needed to fulfill this aim (a) the technique needs to be able to detect every action potential (b) from every neuron (c) for a long period of time (d) from an entire network. Neural activity has been shown to produce fast intrinsic optical signals that are the result of refractive index changes causing light scattering and birefringence associated with membrane depolarisation. To date no one has successfully managed to exploit these intrinsic optical signals in a practical robust recording system. Surface plasmon resonance (SPR) is a technique that can detect extremely small changes in refractive index and is capable of detecting this membrane localised refractive index change with a high spatio-temporal resolution.